THE ESSENCE OF THE CONCEPT OF VALUES AND THEIR ROLE IN YOUTH SPIRITUALITY - Umarov Hamdam Tukhtaevich (Modern American Journals, 2025)
This article analyzes the essence of the concepts of "value" (qadr) and "values" (qadriyat) and their significance in human life. The types of values—material and spiritual, personal, national, and universal—are discussed. Particular attention is paid to the role and importance of universal values in shaping the spiritual outlook of youth. The article also examines the views of various scholars on values and the classifications found in the science of axiology. Furthermore, issues related to the crisis of values and its negative impact on the moral and spiritual development of the younger generation are highlighted.
Keywords: Concept of value and values, value crisis, axiology, material values, spiritual values, personal values, universal values, national values, classification of scholars' views on values.